Content Recommendation Algorithm for Educational Robotics Lesson Plans - Moura, Merciana Gonçalves Pereira; Pereira, Aylane Santos; Gonçalves, Luiz Marcos Garcia; Curvelo, Carla Da Costa Fernandes (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Educational robotics is a teaching methodology that uses robotics to encourage students to learn curriculum content and bring technology into the classroom. In order to widely apply educational robotics in schools, however, it is necessary to have trained teachers who are able to plan and execute educational robotics classes. For this purpose, RepoEduc was developed, a web repository that stores educational robotics lesson plans. However, knowing the wide application of robotics in the classroom, we understand that we may have too much content stored in this repository, and that it is therefore important to personalize the users’ experience when using the system, presenting them with information that is relevant and of interest to them. With this purpose, this work describes the development of a content recommendation system focused on educational robotics, associated with Repo-Educ, whose main objective is to select contents of interest to the user and present them in a way that ensures that the contents of the repository are presented according to their relevance, considering the profile of each user. The system has been fully developed and tested, with good results. Validation and acceptance tests will be carried out as soon as Repo-Educ is available for use.